FlexO2: A patient-controlled oxygen flow selector improving autonomy and daily function in long-term oxygen therapy (LTOT) - Michael Runold; Ingegerd Karlsson; Magda Borén (Respiratory Research)
Abstract Background Chronic respiratory insufficiency associated with severe resting hypoxemia necessitates long-term oxygen therapy (LTOT), yet existing devices often impede daily activities due to cumbersome flow adjustments, increasing reliance on caregivers. FlexO2 is a novel mechanical regulator that enables switching between preset oxygen flow rates for rest and activity. This proof-of-concept study evaluated its impact on patient autonomy, physical activity, and quality of life. Methods In a consecutive, non-randomized pre-post intervention proof-of-concept study at Karolinska University Hospital, 26 patients on LTOT (median age 77; 69% COPD) used FlexO2 for three months. The device, worn around the neck, allowed patients to self-adjust oxygen doses without accessing the concentrator. Outcomes included ease of use measured by visual analogue scale (VAS), physical activity levels, COPD Assessment Test (CAT), EQ-5D-5 L index, and frequency of dose adjustments. Results Ease of dose adjustment increased from a VAS score of 14 to 92 (p < 0.001), with 92% of patients reporting improved ease of adjustment (baseline 7.7%; p < 0.001). Daily adjustment frequency doubled (8 to 15; p = 0.001). Patient-reported activity capacity improved from a VAS of 11 to 80 (p < 0.001). Quality-of-life scores measured by VAS increased from 19 to 61 (p < 0.001), while CAT scores decreased from a median of 26.0 to 22.5 (p = 0.05). The EQ-5D-5 L index remained stable (0.68 to 0.70; p = 0.7), although 38% of patients showed individual improvements. Device usability was high (83% satisfaction), though 15% reported tubing tangling or airflow issues. Conclusion FlexO2 significantly improved the ease of oxygen dose adjustment and physical activity capacity, potentially enhancing patient autonomy in LTOT. While overall patient-reported quality-of-life scores improved, objective quality-of-life outcomes remained stable. Further studies are warranted to explore long-term clinical outcomes and the potential impact on caregiver burden.